Hippocampus and cornu ammonis: mythonyms that prevail in Terminologia Anatomica, Terminologia Neuroanatomica, and Terminologia Histologica - Duque-Colorado, Jhonatan; García-Orozco, Laura; Castillo-Martínez, Alicia; Sol, Mariano del (Frontiers in Neuroanatomy, 2025)
Julius Caesar Arantius first described the hippocampus and proposed the term hippocampum. Years later, French anatomists called the structure ram’s horns, and a decade later, it was named cornu ammonis. Although both concepts were first associated with the same structure, their use has expanded to include different but related structures. This situation can make understanding and applying the terminology more difficult. The objective of this work was to determine the presence of the terms hippocampus, cornu ammonis and their variants in Terminologia Anatomica, Terminologia Neuroanatomica, and Terminologia Histologica, evaluating their congruence in said terminologies, in addition to examining the etymology of both terms. We searched Terminologia Anatomica, Terminologia Neuroanatomica, and Terminologia Histologica for terms containing the concepts hippocampus, cornu ammonis, and their derivatives. We analyzed the terms hippocampus and cornu ammonis from their etymology by examining several Latin texts. This analysis included the dissection of the hippocampus and fornix and a review of the RAT rules. The etymological analysis indicated that the hippocampus refers to a sea horse; however, the term also has a mythological background. Cornu ammonis, on the other hand, refers to the horns of an Egyptian god. The terminologies present discrepancies regarding the terms derived from hippocampus and cornu ammonis. Although both terms appear in various terminologies, they are mythonyms that fail to describe the structure they refer to or meet the requirements set by FIPAT.